Fabrication Of Low Cost Sensitized Solar Cell Using Natural Plant Pigment DYES - Azhari, Muhamad Azwar; Arith, Faiz; Ali, Nurfadzillah; Rodzi, Shekin; A. Karim, Nor Khalilah (Asian Research Publishing Network (ARPN), 2015)
-